The abilities of recruiters and methodology of the selection process as factors for employment - Angeloska-Galevska, Natasa; Galevska, Elena; Stefanova, Pavlina (Ревија за социјална политика/Journal of Social Policy, 2023)
The strategies for recruitment and selection of candidates are increasingly evolving as the main factors for the successful employment of candidates. In a society where companies compete for suitable candidates, recruiters have the responsible role of representing the company and making the first impression. The recruiters are the link between the labour population and the labour market. The abilities that recruiters possess and the selection strategies they use are a crucial part of this interconnection. The aim of the paper is to analyse what methodology recruiters use in the selection process, as well as the main abilities they must possess as a factor to create a match between suitable candidates and the job position. By studying the point of view of recruiters and candidates, we describe the variety of strategies used in the process of hiring candidates. With the scope of ensuring a positive candidate experience as well as a pleasant recruitment process in a limited labour market such as the current one, recruiters need to possess strong soft skills, especially in terms of communication, active listening, and empathy. When deciding upon the methodology they need to work closely together with the hiring managers and HR managers and choose the most adequate steps such as interviews, personality tests, and various tasks. Empirical results from the study give a glimpse of the methodology and tools used in sourcing and selecting suitable candidates and provide consideration of other practices to be developed in the recruitment process in order to increase and improve employment.
Keywords: recruiters; methodology; selection; employment